'Min Stemme' - a Collective Effort for Developing Web-Based Content for Teaching and Learning about Democracy and Democratic Values in Norwegian Schools and Kindergartens - Susanne Kjekshus Koch; Kristine Sevik (Universitetsforlaget, 2013)
The website Min Stemme has been developed for the centennial of women's right to vote and universal suffrage in Norway in 2013 and the bicentennial of the Constitution of Norway in 2014. It is a website for teaching and learning about democracy and inspiring democratic participation in K-13 (preschool through upper secondary school). Institutions and organizations that already produce and distribute resources related to the two jubilees or relevant topics provide most of the content to the website.